Effectiveness of Mathematics-Gammified Applications for Learners Interactive Numeracy Growth (Math-Galing) in Enhancing the Academic Performance of Grade 11 Learners - Monique E. Malabayabas; Alberto D. Yazon; John Frederick B. Tessoro; Karen A. Manaig; Sherwin B. Sapin (Research Synergy Foundation, 2024)
This study determined the effectiveness of the academic performance of Grade 11 learners using the Mathematics Gamified Application for Learner's Interactive Numeracy Growth (Math-GALING). This study used a quasi-experimental design. The participants of the study were selected through a match-pairing technique based on the results of their pretest among Grade 11 students, resulting in 29 pairs. These two groups of students, one from the Accountancy, Business, and Management strand and the other from the Humanities and Social Sciences strand, comprised the experimental and comparison groups, respectively. The participants' pretest, posttest, and formative test performances was evaluated using the mean and standard deviation. Similar to how independent t-tests were used to quantify the extent of the difference between two sets of scores, Cohen’s d was used to determine the significance of the difference between the pretest and posttest results. The salient findings from the data were as follows: there is always an opportunity for improvement, particularly when the goal is to enhance teaching and learning processes to provide students with quality education. This study could conclude that using a gamified learning application (Math-GALING) in the teaching of statistics and probability enhanced learners’ performances. It was found that the designed gamified learning application enhanced students’ academic performances.